The Apocrypha: a guide - Goff, Matthew J. (Guides to sacred texts, 2024)
This text is an introduction to the Apocrypha and related literature, written for a non-specialist audience. Each chapter focuses on a specific book, examining its core themes and ideas, the cultural and historical context of its composition, and its later reception. Anyone who is interested in learning more about the Apocrypha can benefit from reading this book.